Landscape Ecology in Agroecosystems Management - Ryszkowski, Lech (CRC Press, 2009)
Successful management of agricultural landscapes depends on the recognition of the relationships between the processes and the structures that maintain the system. The rapidly growing science of Landscape Ecology quantifies the ways these ecosystems interact and establishes a link between the activities in one region and repercussions in another. Although science continuously yields new environmentally friendly agricultural technology, the sustainable development of a system will ultimately depend on a farmer's ability to understand and utilize these advances. The results presented in this book highlight the options for controlling threats and present guidelines for the implementation of environmentally friendly landscape management.